Variation with age in the pattern of type X collagen expression in normal and scoliotic human intervertebral discs. - Aigner, T; Gresk-otter, K; Fairbank, J; von der Mark, K; Urban, J (1998)
The distribution and expression of type X collagen, a calcium-binding collagen, which is a marker of hypertrophic chondrocytes and thought to be involved in cartilage calcification, was examined in situ in nondegenerate (grade I or II) human discs taken at autopsy over a wide age range (fetal->80 years) and also in scoliotic discs removed at surgery. In the fetal vertebral column, type X collagen was strongly expressed in the hypertrophic chondrocytes of the endplate, but was not seen in other areas. In the cartilaginous endplate of adults, it was found over the whole age range examined, with intensity increasing with age. In the disc matrix itself, type X collagen was demonstrated around individual cells from all individuals older than 50 years, but not in any fetal or autopsy disc from individuals younger than 40 years. In scoliotic discs, however, focal type X collagen expression was seen in 3/8 patients younger than 40 years including one 12-year-old. No type X collagen was found in the outer annulus in any autopsy or scoliotic disc, supporting the idea that cells of the outer annulus are phenotypically distinct from cells of the inner annulus and the nucleus. Our results demonstrate for the first time that type X collagen is a possible gene product of the intervertebral disc cells and a potential biochemical component of the disc matrix. They indicate that with age or in scoliosis, some cells from the inner annulus or nucleus of the disc differentiate to the hypertrophic chondrocyte phenotype. This might be the initiating event for the abnormal calcification described in aged and scoliotic discs in other studies.